La Grande Collecte 1914-1918 aux Archives nationales - Isabelle Aristide-Hastir; Elsa Marguin-Hamon (In Situ)
The operation called ‘La Grande Collecte’, the great collection, is an initiative of the French national library aimed at collecting and copying private documents relating to the First World War. This operation was carried out from 9 to 16 November 2013 and met with considerable success both at the national archives and throughout the network of fifty libraries which participated in the operation. Private individuals were invited to bring family documents relating to the First World War, documents which could be digitised and published on line on the site Europeana Collections 1914-1918, along with their own account of the origins of the papers. The documents are therefore conserved only in digital form, although many donors in the end preferred to give the originals to the archive services, aware that the papers are now fragile and that their conservation within the family was perhaps not guaranteed. The harvest, at first sight, is both diversified and repetitive: letters, post cards, photographic portraits of soldiers, military service record books, private notebooks, drawings and so on. But taken as a whole and forming part of a shared heritage of memory associated with exceptional events (perceived as such by the witnesses), the collection now forms a national treasure without equivalent at the national archives.